Compression and venous ulcers. (March 2013) - Stücker, M; Link, K; Reich-Schupke, S; Altmeyer, P; Doerler, M
Compression therapy is considered to be the most important conservative treatment of venous leg ulcers. Until a few years ago, compression bandages were regarded as first-line therapy of venous leg ulcers. However, to date medical compression stockings are the first choice of treatment. With respect to compression therapy of venous leg ulcers the following statements are widely accepted: (1) Compression improves the healing of ulcers when compared with no compression; (2) Multicomponent compression systems are more effective than single-component compression systems; (3) High compression is more effective than lower compression; (4) Medical compression stockings are more effective than compression with short stretch bandages. Healed venous leg ulcers show a high relapse rate without ongoing treatment. The use of medical stockings significantly reduces the amount of recurrent ulcers. Furthermore, the relapse rate of venous leg ulcers can be significantly reduced by a combination of compression therapy and surgery of varicose veins compared with compression therapy alone.